Economic Analysis Affecting Tourist Demand on the Number of Visitors to the Gondoriah Pariaman Beach Tourism Object - Suhatman Suhatman; Nasfi Nasfi (Yayasan Ilomata, 2021)
This study aims to determine the economic analysis that affects tourist demand on the number of visitors to tourist attractions during 2014-2019, with research at Gandoriah Beach, Pariaman City. The independent variables are motivation (x1), price (x2), tourist attraction (x3), ease of visit (x4), image (x5). The dependent variable is the number of visitors (Y). The sample in this study were 96 tourists who visited Gandoriah Beach. Data were collected using questionnaire data and primary data. Hypothesis testing using analysis, regression, t test, F test and determination were processed using the SPSS 18 for windows program. The results show that partially motivation has no effect on the number of visitors, price has no effect on the number of visitors, tourist attraction affects the number of visitors, ease of visit affects the number of visitors, and image affects the number of visitors. Simultaneously the independent variable has a significant effect on the dependent variable with an F value of 38.086 with a probability of 0.000 <0.05. The joint contribution was 66.1%.